Mechanical Behavior and Acoustic Emission Characteristics of Sandstone Under Different Cyclic Loading and Unloading Disturbance Rates - Pengpeng Wang; Liu Bin; Chunwei Ling; Qingshan Ren; Baohui Xu; Xuyu Hu (Energy Science & Engineering)
ABSTRACT The frequency of dynamic disasters is escalating in deep coal mining, with an increasing number of disasters induced by the combined static and dynamic loading. To investigate the mechanical behavior of deep sandstone under mining, cyclic disturbance, uniaxial cyclic loading, and unloading tests with equal amplitude were conducted at four different disturbance rates on the basis of static loading. The influence of loading and unloading disturbance rates on mechanical properties, fracture characteristics, acoustic emission (AE) temporal‐spatial evolution, and fractal characteristics of AE spatial distribution were analyzed. The results show that the peak strength of rock samples initially decreases and then increases as the disturbance rate increases. During the cyclic loading and unloading disturbance stage, AE exhibits a significant Kaiser effect under different disturbance rates. The higher the disturbance rate, the greater the number of cycles with high amplitude AE, but fewer high amplitude AE occur during the loading to peak failure stage. The increment of the damage variable is positively correlated with the loading and unloading disturbance rate overall. The AE spatial fractal dimension in rock samples decreases under different loading and unloading disturbance rates, stabilizing at a range of 2.1–2.3. As the loading and unloading disturbance rate increases, the decreasing magnitude in fractal dimension during the cyclic loading and unloading stage first increases and then decreases, with a relatively smaller decrease during the loading to peak failure stage.